Electronic Structure and Room Temperature Ferromagnetism in Gd‐doped Cerium Oxide Nanoparticles for Hydrogen Generation via Photocatalytic Water Splitting. Issue 5 (7th January 2019) - Soni, Swati; Chouhan, Neelu; Meena, Rajesh Kumar; Kumar, Sudhish; Dalela, Bhavna; Mishra, Monu; Meena, Rajendra Singh; Gupta, Govind; Kumar, Shalendra; Alvi, Parvez Ahmad; Dalela, Saurabh
Abstract: Enhanced visible light photocatalytic activity of Gd‐doped CeO2 nanoparticles (NPs) is experimentally demonstrated, whereas there are very few reports on this mechanism with rare earth doping. All‐pure and Gd‐doped CeO2 NPs are synthesized using a coprecipitation method and characterized using X‐ray diffraction (XRD), absorption spectroscopy, surface‐enhanced Raman Spectroscopy (SERS), X‐ray photoelectron spectroscopy (XPS), and superconducting quantum interference device (SQUID). The effect of Gd‐doping on properties of CeO2 is discussed along with defects and oxygen vacancies generation. The XRD confirms the incorporation of Gd 3+ at the Ce 3+ /Ce 4+ site by keeping the crystal structure same. The average particle size from transmission electron microscopy (TEM) images is in the range of 5–7 nm. The XPS spectra of Ce 3d, O 1s, and Gd 4d exhibits the formation of oxygen vacancies to maintain the charge neutrality when Ce 4+ changes to Ce 3+ . The gradual increase in hydrogen production is observed with increasing Gd concentration. The observed results are in good correlation with the characterization results and a mechanism of water splitting is proposed on the basis of analyses. The absorption spectra reveal optical band gap (2.5–2.7 eV) of samples, showing band gap narrowing leads to desired optical absorbance and photoactivity of NPs. Abstract : Visible light photocatalytic activity of Gd‐doped CeO2 nanoparticles are experimentally demonstrated, with a gradual increase in hydrogen production with Gd‐concentration. The particle size of photocatalyst, binding energies, oxygen vacancy concentrations, band gap, etc., are collectively responsible for the increase in hydrogen generation activity with increasing Gd‐doping concentration in ceria.